2019
DOI: 10.1111/ijag.14776
|View full text |Cite
|
Sign up to set email alerts
|

Features of electronic polarizability and approach to unique properties in tellurite glasses

Abstract: Tellurite glasses showing unique properties such as low phonon energy and high linear and nonlinear optical properties have been considered as promising materials for photonic device applications. The present article reviews the current status of the electronic polarizability in binary and ternary tellurite glasses and approaches their unique properties. Tellurite glasses consisting of basic modifier oxides (eg, Na2O, ZnO) and basic conditional glass forming oxide (TeO2) exhibit the features of high electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 99 publications
(331 reference statements)
1
41
0
Order By: Relevance
“…In the so‐called bond energy criterion proposed by Sun, 37 the glass‐forming acidic oxide SiO 2 has a large single bond strength B M–O of a chemical bond Si–O, B M–O = 443.5 kJ/mol, and contrary, the modifier basic oxides have small single bond strengths, e.g., B M–O = 84 kJ/mol for Na 2 O. Dimitrov and Komatsu 15,38,39 proposed an approach for the calculation of the average single bond strength of glasses based on the Sun's data, indicating that the average single bond strength of silicate glasses decreases with increasing modifier's content. They also reported that silicate glasses have large chemical bond strengths compared with GeO 2 ‐based and TeO 2 ‐based glasses, e.g., B M–O = 372 kJ/mol for 20Na 2 O–80SiO 2 glass, B M–O = 291 kJ/mol for 20Na 2 O–80GeO 2 glass, and B M–O = 245 kJ/mol for 20Na 2 O–80TeO 2 glass 4 …”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…In the so‐called bond energy criterion proposed by Sun, 37 the glass‐forming acidic oxide SiO 2 has a large single bond strength B M–O of a chemical bond Si–O, B M–O = 443.5 kJ/mol, and contrary, the modifier basic oxides have small single bond strengths, e.g., B M–O = 84 kJ/mol for Na 2 O. Dimitrov and Komatsu 15,38,39 proposed an approach for the calculation of the average single bond strength of glasses based on the Sun's data, indicating that the average single bond strength of silicate glasses decreases with increasing modifier's content. They also reported that silicate glasses have large chemical bond strengths compared with GeO 2 ‐based and TeO 2 ‐based glasses, e.g., B M–O = 372 kJ/mol for 20Na 2 O–80SiO 2 glass, B M–O = 291 kJ/mol for 20Na 2 O–80GeO 2 glass, and B M–O = 245 kJ/mol for 20Na 2 O–80TeO 2 glass 4 …”
Section: Methodsmentioning
confidence: 98%
“…Equation () combining α O2− ( n o ) with Λ( n o ) is a proposal by Duffy 3 and indicates the average oxide ion polarizability of a given glass. The estimation of α O2− ( n o ) and Λ( n o ) has been applied to various oxide glasses 4,5,8,9,15 . Compared with the probe ion method, the refractive index‐based optical basicity determined from the Lorentz–Lorenz formula method would be regarded as the average (whole, not local) electronic polarizability of a given glass.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another idea for the effective relaxation of stresses at the interface between β‐GMO crystals and surrounding super‐cooled liquids is proposed by Kotaka et al, 48 in which B 2 O 3 oxide in Gd 2 O 3 ‐MoO 3 ‐B 2 O 3 glasses is replaced partly with TeO 2 oxide. It is known that B 2 O 3 is the strong glass‐forming oxide, that is, a strong chemical bond strength of B‐O bonds, and TeO 2 belongs to the category of the fragile glass‐forming oxide, that is, a weak chemical bond strength of Te‐O bonds 61 . Generally, B 2 O 3 ‐based glasses consist of tetrahedral BO 4 and trigonal BO 3 units, and TeO 2 ‐based glasses include trigonal bi‐pyramidal TeO 4 and trigonal pyramidal TeO 3 units.…”
Section: Crystallization Of β’‐Gd2(moo4)3 In Glassmentioning
confidence: 99%